First-principles calculations to investigate physical properties of orthorhombic perovskite YBO3 (B = Ti & Fe) for high energy applications. Issue 7 (31st January 2023) - Rached, Ahmed Azzouz; Ouadha, Ismail; Husain, Mudasser; Rached, Habib; Rekab-Djabri, Hamza; Bentouaf, Ali; Hadji, Tariq; Sfina, Nourreddine; Albawali, Hind; Tirth, Vineet; Amin, Mohammed A.; Rahman, Nasir
Abstract : Orthorhombic oxide perovskite compounds are very promising materials for the applications of optoelectronics and thermal barrier coating. Abstract : Orthorhombic oxide perovskite compounds are very promising materials for the applications of optoelectronics and thermal barrier coating. This work represents a numerical simulation of YBO3 compounds through the first-principles ab initio approach. The electronic and magnetic properties are investigated employing the general gradient approximation (GGA) coupled to the integration of the Hubbard U-term which is the GGA + U. The Ti and Fe-based YBO3 perovskite compounds are found to be actively promising within the ferromagnetic configuration and their lattice parameters are consistent with the previous studies. The calculations of formation energy signify that the compounds YBO3 are stable thermodynamically. The electronic properties are computed and evaluated by the band structure and density of states for both compounds and the results depict that these materials are ferromagnetic half-metallic. Mechanically these compounds are stable, ductile, anisotropic, and hard to scratch. The thermal properties are evaluated for YBO3 (B = Ti and Fe) compounds up to a temperature range of 2000 K. This work can open new opportunities for further exploration in this field.